La science au(x) miroir (s) du prince. Savoir et pouvoir dans l'espace arabo-musulman d'hier et d'aujourd'hui - Abdel Wedoud Ould Cheikh (Revue des Mondes Musulmans et de la Méditerranée)
The sultan and the scholar are two central figures in the « sultanic culture » understood within the context of norms and values which present a certain unity in the Arab-Muslim world. There is a fundamental tension between these two figures, the learned scholar being the only authorized figure to preach to the holder of power in the name of knowledge and justice. In today's reality concerning the Arab-Muslim countries, illustrated here by the case of Mauritania, the growing body of education that is, at the same time, strongly impregnated with tradition as well as socially devaluated, undoubtedly contributes toward the emergence of an Islamist anti-establishment domain which, within a collective mode, is found in the continuity of the admonishment framework of the learned scholar who opposes the abuses of the sultan.